Purification of Urban Sewage River Using a Biological Aerated Filter with Sponge Iron and Ceramsite Mixed Fillers - Yi Wu; Jun Dai; Qiong Wan; Guobin Tian; Dongyang Wei (Advances in Civil Engineering)
Filler plays an important role in biological sewage treatment technology. In the purification of urban sewage river, the single sponge iron filler is easy to harden. The combination of sponge iron and ceramsite can hinder the hardening and improve the removal efficiency. In this paper, scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to characterize the fillers. The removal efficiency experiments were carried out through the self-designed biological aerated filter (BAF) reactor with sponge iron and ceramsite mixed fillers, and the microorganisms attached to the surface of the biological fillers were qualitatively and quantitatively identified through 16S rDNA. The results indicate that the presence of Fe3O4, Fe2O3, Fe3C, and Fe2CO3 in sponge iron determines that sponge iron has strong reducibility and provides electrons for efficient denitrification. NaAlSi3O8 in ceramsite filler plays a significant role in phosphorus adsorption. In #3, #4, and #5 reactors (the mass ratios of sponge iron and ceramsite were 1 : 1, 3 : 1, and 1 : 3, resp.), the removal efficiencies of mixed fillers are good on chemical oxygen demand (COD), total phosphorus (TP), and nitrogen (N), and the more the ceramsite fillers in the reactors are, the higher the microbial abundance and diversity are. The mixture of sponge iron and ceramsite can be used to purify urban sewage river. A scientific basis to purify the polluted water body of urban rivers in situ is thus provided.